Customer Engagement, Customer Satisfaction, Customer Commitment And Customer Loyalty - Pratama, Mario Putra; Ramli, Abdul Haeba; Mariam, Siti (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This research is quantitative research with a causal relationship to determine the direct influence customer engagement, customer satisfaction, customer commitment to customer loyalty and knowing the indirect effects, customer engagement, customer satisfaction, customer commitment to customer loyalty on the Tokopedia application. Data collection was carried out using the information gathering method through a survey with a questionnaire. The population in this study is someone who has used Tokopedia, regularly uses Tokopedia, lives in Jabodetabek and is at least 17 years old. The questionnaire collected 120 respondents using the Hair et al. (2019) Questionnaires collected from 120 respondents. The sampling method used is non-probabilitysampling with techniques purpose sampling. Based on the research results, 7 hypotheses can be accepted, namely customer engagement influential customer commitment, customer satisfactioninfluential customer commitment, customer engagement influential customer loyalty, customer satisfaction influential customer loyalty, customer commitment influential customer loyalty, customer engagement influential customer loyalty in mediation customer commitment, customer satisfaction influential customer loyalty mediated customer commitment. Therefore, it is important for the Tokopedia platform to improve customer engagement which can improve customer loyalty. The aim of this research is to determine the direct effect customer engagement, customer satisfaction, customer commitment to customer loyalty and also to determine the indirect influence of customer engagement, customer satisfaction, as well as customer commitment to customer loyalty shown to consumers using the Tokopedia application. Keywords: customer engagement, customer satisfaction, customer commitment, customer loyalty